"Metal elements and pesticides as risk factors for Parkinson's disease - A review". (2021) - Ullah, Inam; Zhao, Longhe; Hai, Yang; Fahim, Muhammad; Alwayli, Dhafer; Wang, Xin; Li, Hongyu
Graphical abstract: Highlights: Common miRNA association between Parkinson's Disease (PD) and pesticides exist. Pesticide-deregulated miRNAs affect PD-related molecules, e.g. α-synuclein. There exist an association between essential, non-essential metals and PD. UPS and mitochondrial impairment, oxidative stress, gene mutation and α-Syn aggregation are prime mechanisms involved in essential, non-essential metals neurotoxicity in PD. Abstract: Essential metals including iron (Fe) and manganese (Mn) with known physiological functions in human body play an important role in cell homeostasis. Excessive exposure to these essential as well as non-essential metals including mercury (Hg) and Aluminum (Al) may contribute to pathological conditions, including PD. Each metal could be toxic through specific pathways. Epidemiological evidences from occupational and ecological studies besides various in vivo and in vitro studies have revealed the possible pathogenic role and neurotoxicity of different metals. Pesticides are substances that aim to mitigate the harm done by pests to plants and crops, and are extensively used to boost agricultural production. This review provides an outline of our current knowledge on the possible association between metals and PD. We have discussed the potential association between these two, furthermore the chemical properties, biological and toxicological aspects as well as possible mechanisms of Fe, Mn, Cu, Zn, Al, Ca, Pb, Hg and Zn in PD pathogenesis. In addition, we review recent evidence on deregulated microRNAs upon pesticide exposure and possible role of deregulated miRNA and pesticides to PD pathogenesis.